Position multisituée et récursivité - Anne-Christine Trémon (Ateliers d'Anthropologie)
The ethnographic relationship established with inhabitants of an old Chinese emigrant village was modelled by the ethnographer’s multisituated position, resulting from a previous study conducted among the diaspora from that village. This link with a segment of the diaspora exercised a recursive effect on the materials gathered in the field. Efforts to broaden the research beyond that segment, along with the realisation of this recursivity, made it possible to better understand the diasporic relationship, at the cost of a shift: the research no longer concerned only the study of the change in the relationship with the diaspora in the context of China’s social and economic changes, but also concerned local understandings of these changes in the context of that relationship. This article thus ends up reflecting on how the anthropologist’s position in the field can result in displacements of the context of the subject of study.